Influência de fatores ambientais e espaciais sobre as taxocenoses e ninhos conspícuos de térmitas (Blattodea: Isoptera) em um gradiente longitudinal - Ernesto, Matilde Vasconcelos (2018)
Changes in species richness, abundance and composition of assemblage due to changes in environmental and spatial variables in different habitats are common and inherent to taxa. Termites are eusocial insects considered ecosystem engineers and their conspicuous nests are striking elements of the structural composition of tropical ecosystems. Our study aimed to relate environmental and spatial variables to the distribution of assemblage and conspicuous termite nests in areas of Atlantic Forest and Caatinga over a longitudinal gradient of 500 km. Eight areas distributed in Paraíba were investigated and spatial (latitude, longitude and altitude) and environmental data (climate, physical and chemical composition of the soil and vegetation structure) were collected in each of them. For the faunistic survey, 30 plots of 5x2m were sampled, totaling 300m² per area. The conspicuous nests were analyzed from six plots of 65x20m per area. Linear mixed-effects models and generalized linear mixed models were constructed. Seventy morphospecies of termites were recorded, belonging to 28 genera and three families. Twelve species were builders of conspicuous nests, among which nine are builders of arboreal nests and three of epigeal nests. The vegetation structure (canopy cover and amount of litter) was an important predictor for the distribution of assemblage and conspicuous termite nests. The vegetation directly acts in the availability of resources and environmental stability. Precipitation and maximum temperature influenced some dependent variables analyzed, such as total species richness, species richness of Syntermitinae and trophic group III, as well as density of conspicuous nests. These variables, along with evapotranspiration, are closely related to the net primary productivity, which can directly influence the distribution of termites. Some soil components (such as pH, amount of Al+3 and Mg+2) were important predictors for trophic group III, Apicotermitinae and Syntermitinae. Other components, such as N and P content, were important predictors for the volume and density of conspicuous nests, respectively. In general, soil-feeding termites are more vulnerable to fluctuations in the microclimate in which they are inserted. Longitude was an important predictor of the species richness of termite builder species and promoted some influence also on the composition of species. This variable encompasses several other factors, and may also be related to net primary productivity. Two builder species were considered to be widely distributed: Microcerotermes indistinctus and Nasutitermes corniger. Nests of M. indistinctus were influenced by the amount of sand in the soil and the longitude, while nests of N. corniger were not influenced by any of the variables tested. Kalotermitidae, Rhinotermitidae and Termitinae also did not present significant relations with any of the predictive variables tested, which may suggest that historical factors are the determinants of the distribution of these taxa and of the nests of N. corniger or that there is an influence of another predictor variable not tested in the present study. In addition, a survey of the termite species in Paraíba was carried out during the present study. Fifty-four species (with defined taxonomic status) were identified for the state. The greatest numbers of termite species ever reported for the Atlantic Forest and Caatinga all over Brazil, for a single area, were recorded in two of the studied fragments in Paraíba. These results highlight the relevance of the termite fauna found in the state of Paraíba compared to the other areas in northeastern Brazil.